(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The world’s population and economic growth have exploded in the last 50 years, indicating a constant need for natural resources to raise millions of people’s living standards due to the current linear economic model’s demand and supply curves for natural resources and waste absorption. The present circumstance necessitates a closed economy, a restorative, zero-waste economic model that maximises resource utilisation. The necessity, origin, idea, and business models of circular economy. The report examines the role of circular economy efforts in achieving SDGs. Finally, it discusses several countries’ circularity programs, with a focus on India, to improve resource efficiency and reduce waste. Policy and corporate advocacy groups are presently promoting the Circular Economy. Despite its ambitious and controversial message, Circular Economy research is emerging. The paper’s two main goals are to identify, discuss, and develop the growing literature’s definitions, and to recommend a beginning research method for the Circular Economy. Our research demonstrates that the current Circular Economy effort focuses on the fundamental physical flows of materials and energy in production and consumption systems. The existing literature focuses on metrics, techniques, instruments, and computations. The circular economy’s paradigmatic potential remains undiscovered due to unknown assumptions about values, societal structures, cultures, and underlying worldviews. To categorise and organise studies on Circular Economy, the study proposes a model. The model can assist reduce the observed imbalance and improve the Circular Economy’s contribution to a more sustainable global society.